The Practice of Marriage of Sampang Shia Refugees in Puspa Agro, Sidoarjo: Barriers and Challenges to Obtaining Family Administration Rights - Mulyani, Maulidia (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2022)
Abstract: This article examines the constraints and challenges of the Sampang Shia refugees in Puspa Agro, Sidoarjo, in carrying out marriages and obtaining family administration rights. The data source in this article is based on field data obtained through observation and interviews and is supported by library data. Using resilience theory, this article seeks to answer two fundamental issues: first, what are the barriers faced by the Shia refugee group in Sampang in entering into marriages and obtaining family administration rights?; second, what is the strategy used by the Sampang Shiite group in obtaining family administration rights? Using socio legal, this article finds that Shi'a refugees face obstacles and challenges in consummating marriages and obtaining family administration rights as a result of the Sunni-Shia conflict that does not subside. They did not receive marriage guidance and also could not get married in front of KUA officers due to the long distances and high costs. In an effort to obtain administrative rights for their family, they made efforts to adapt to the existing situation. They carry out marriage guidance by asking the lokal ustaz for advice, submitting files to make a marriage certificate and taking part in the marriage registration program with an escort. Abstrak: Artikel ini mengkaji kendala dan tantangan para pengungsi Syiah Sampang yang ada di Puspa Agro, Sidoarjo, dalam melakukan perkawinan dan mendapatkan hak administrasi keluarga. Sumber data dalam artikel ini didasarkan pada data-data lapangan yang diperoleh melalui observasi dan wawancara dan didukung dengan data kepustakaan. Menggunakan teori resiliensi, artikel ini hendak menjawab dua hal mendasar: pertama, apa saja kendala yang dihadapi kelompok pengungsi Syiah Sampang dalam melakukan perkawinan dan mendapatkan hak administrasi keluarga?; kedua, bagaimana strategi yang digunakan oleh kelompok Syiah Sampang dalam mendapatkan hak administrasi keluarga? Menggunakan socio legal, artikel ini menemukan bahwa para pengungsi Syi’ah menghadapi kendala dan tantangan dalam melakukan perkawinan dan mendapatkan hak administrasi keluarga sebagai akibat dari adanya konflik Sunni-Syiah yang tidak kunjung mereda. Mereka tidak mendapatkan bimbingan pernikahan dan juga tidak dapat melakukan pernikahan di depan petugas KUA disebabkan jarak tempuh yang jauh dan biaya yang mahal. Dalam upaya untuk mendapatkan hak administrasi keluarga mereka melakukan upaya adaptasi dengan situasi yang ada. Mereka melakukan bimbingan nikah dengan cara meminta nasihat kepada ustadz setempat, menyetorkan berkas untuk pembuatan akta nikah dan mengikuti program isbat nikah dengan pengawalan.